The Effect of Buzz Group Based Blended Learning to Improve Students Cognitive Learning Outcomes on Thermochemical Materials - Hidayah, Chaerul; Rahmawan, Setia (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Thermochemistry is considered difficult because students are required to be able to apply mathematical equations in a calculation. Coupled with the use of the lecture method, this makes students less active and bored with learning, so the learning outcomes are low. Therefore, appropriate teaching strategies are needed so that learning becomes effective, namely using a buzz group based on blended learning where there is collaboration and discussion between students with the integration of digital technology. This study aimed to determine the effect of buzz groups based on blended learning to improve students' cognitive learning outcomes in thermochemical material. This research is experimental research, with a quasi-experimental design in the form of a pretest-posttest control group. The research was conducted at MA Minhajut Tholabah, Purbalingga. The sampling technique chosen was saturation sampling, with a sample of class XI MIA 1 as the experimental class and class XI MIA 2 as the control class. The research instrument uses test questions and questionnaires. The function of this instrument is to compare the result of learning between the experimental and control classes. The data analysis technique used for testing the hypothesis is the Mann-Whitney test, and the questionnaire uses percentages. Based on the results of the Mann-Whitney test, the significance value was 0.03 <0.05, which means that H0 is rejected. The average of the student response questionnaire was 77%. This result can be categorized as interesting. It was concluded that there was an influence of the blended learning-based buzz group method to improve students' cognitive learning outcomes in thermochemical material, and the results of the response questionnaire indicated that students were interested in using this method.